Drinking behaviours and alcohol preferences of female and male students at a Polish university in 2000–2016. (4th May 2019) - Podstawski, Robert; Wesołowska, Elżbieta; Choszcz, Dariusz; Markowski, Piotr; Klimczak, Jarosław
Abstract: The aim of this study was to describe and compare the drinking behaviours and alcohol preferences of female and male university students. A total of 5514 female and 4264 male students (Poland) participated in the study. Empirical data were collected every 2 years in 2000–2016, with the use of an anonymous questionnaire. The respondents were asked about the frequency of alcohol consumption, the preferred alcoholic beverages and their attitudes towards drinking. Data were analysed statistically by the Kruskal–Wallis test, Dunn's post-hoc test and the Mann–Whitney U test. Around 60–70% of the surveyed students were drinking sporadically, whereas 10–12% abstained from alcohol. Around 9–10% of the subjects had experienced alcohol-induced blackouts. Beer was the most popular alcoholic beverage, and it was consumed by 50–60% of the respondents. Seventy percent of the respondents were of the opinion that alcohol should be available on campus, and they had no intention to abstain from drinking. Both similar trends and inter-gender differences were observed among female and male students, most of whom had liberal attitudes towards alcohol consumption. Vodka continues to be popular among male students. Female students traditionally opted for weaker–strength alcoholic beverages and were more willing to try new types of alcohol.